2016
DOI: 10.18632/oncotarget.10423
|View full text |Cite
|
Sign up to set email alerts
|

miR-130b, an onco-miRNA in bladder cancer, is directly regulated by NF-κB and sustains NF-κB activation by decreasing Cylindromatosis expression

Abstract: Persistent activation of NF-κB signaling is closely related to chronic inflammation and tumorigenesis. Commonly, NF-κB signaling is tightly controlled by multiple feedback loops and regulators, such as the deubiquitinases (DUBs). However, in cancer cells, NF-κB may override these feedbacks through special pathways and lead to the sustained activation. In the present study, we demonstrate that in transitional cell carcinoma (TCC) of bladder, miR-130b plays an oncogenesis role, it enhanced proliferation, invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 44 publications
1
36
0
Order By: Relevance
“…miRNAs 130b-3p, 27b, and 140, which were each elevated on our PCR array during sepsis, have all been shown to regulate inflammation, specifically via NF-jB [21][22][23]26]. After determining which inflammatory miRNAs had a propensity to become elevated in the blood during sepsis, we then reviewed the literature to decide which miRNAs to continue studying for their potential interaction with eCIRP.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs 130b-3p, 27b, and 140, which were each elevated on our PCR array during sepsis, have all been shown to regulate inflammation, specifically via NF-jB [21][22][23]26]. After determining which inflammatory miRNAs had a propensity to become elevated in the blood during sepsis, we then reviewed the literature to decide which miRNAs to continue studying for their potential interaction with eCIRP.…”
Section: Discussionmentioning
confidence: 99%
“…Although the roles of circRNAs remain a mystery, insights into circRNAs have revealed that several circRNAs can function as microRNA sponges (26). In addition, Cui et al (27) revealed that the nuclear factor-κ-B (NF-κB) signaling pathway could directly regulate transcription of miR-130b. Thus, the upstream regulation mechanism of miR-26-5p warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…The TNF‐α‐induced expressions of miR‐130b have been described in both adipocyte and bladder carcinoma cell lines . Through the analyses on the data from semiquantitative real‐time RT‐PCR assays, we found that the increment in the expression level of miR‐130b was in correlation with the elevation in the concentration of TNF‐α utilized to treat cell when the concentration of TNF‐α increased from 0 up to 10 ng·mL −1 .…”
Section: Resultsmentioning
confidence: 88%
“…A). The recent literatures illustrated that NF‐κB mediated the TNF‐α‐upregulated expressions of miR‐130b in both adipocyte and bladder carcinoma cell lines by directly binding to its response elements within the miR‐130b promoters . And it has been generally known that TNF‐α stimulation induced the activation of NF‐κB in Hela cell.…”
Section: Discussionmentioning
confidence: 99%